PHARMACOGNOSTICAL AND ANATOMICAL EVALUATION OF THE SELECTED PARTS OF Strychnos potatorum L.f. - T.V.BINU; B.VIJAYAKUMARI (International Journal of Pharma and Bio Sciences, 2014)
In the present study, selected parts (stem, bark, leaf and seed) of Strychnos potatorum L.f. belonging to the family Loganiaceae were evaluated for the preliminary phytochemicals and anatomical characteristics. Petroleum ether, chloroform, methanol and water were selected as solvents according to increasing order of their polarity. Qualitative analysis of the selected parts confirmed the presence of various primary and secondary plant metabolites such as alkaloids, terpenoids, flavonoids, steroids, phenols, cellulose, starch, tannins, fixed oil and quinone. Anatomical studies include cross sections of the selected parts. This study provided referential botanical and phytochemical information for correct identification of the plant.